2017
DOI: 10.1111/bcp.13356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of serum potassium‐influencing antihypertensive drugs on the risk of out‐of‐hospital cardiac arrest: A case–control study

Abstract: The risk of OHCA is significantly increased in patients who were current users of hypokalaemia-inducing antihypertensives and patients using a combination of antihypertensives with hypo- and hyperkalaemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…Indeed, hypokalemia induces conduction abnormalities, such as increased P wave amplitude and duration, a slight prolongation of the PR interval, atrioventricular block, increased QRS duration, and cardiac arrest . We found all of these electrocardiographic conduction disturbances in our experimental hypokalemia model (Figures ).…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, hypokalemia induces conduction abnormalities, such as increased P wave amplitude and duration, a slight prolongation of the PR interval, atrioventricular block, increased QRS duration, and cardiac arrest . We found all of these electrocardiographic conduction disturbances in our experimental hypokalemia model (Figures ).…”
Section: Discussionsupporting
confidence: 54%
“…However, in this study, our patients with elevated potassium levels had one or more conditions causing hyperkalemia such as comorbid HTN, DM, or CKD, and high rates of certain medications use, including non-steroidal anti-inflammatory drugs (NSAIDs) beta-blockers, CCBs, ACEIs, and ARBs. These findings are concordant with previous reports on the risk factors of hyperkalemia [6,14,15,[47][48][49][50][51][52][53]. Our study as well reported high rates of statins and PPIs to use within hyperkalemic patients.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to non-potassium-sparing diuretics, we observed a 1.4-fold increased CVM in the meta-analysis of the results from the two studies. This is in line with the results of Cooper et al [21] (population: patients with left ventricular dysfunction; outcome: arrhythmic death), Ahmed et al [20] (population: heart failure patients; outcome: long-term mortality), and Alharbi et al [40] (population: cases with cardiac arrest and controls from the general population; outcome: cardiac arrest). However, our results are not directly comparable to these studies because we included a population with a lower cardiovascular risk (e.g., a mix of patients with hypertension and/or heart failure receiving antihypertensive drugs).…”
Section: Discussionsupporting
confidence: 90%